Role of the clock gene homolog aha-1 in the circadian system of Caenorhabditis elegans - Melisa Luciana Lamberti; Francisco Silva; María Eugenia Goya; Claire Y. Bénard; Claire Y. Bénard; Diego A. Golombek; Diego A. Golombek; María Laura Migliori (Frontiers in Neuroscience)
BackgroundCircadian rhythms are endogenous and allow organisms to adapt to external daily rhythms of light, temperature and other environmental factors. Circadian rhythms are regulated by a central clock, which is based on a transcription-translation feedback loop. The AHA-1 protein from Caenorhabditis elegans possesses all conserved domains and shows high homology with the positive elements of the central clock loop, BMAL1 in mammals and CYCLE in Drosophila.MethodsWe studied the possible involvement of aha-1 in the circadian system of adult C. elegans using a bioluminescence-based circadian transcriptional reporter. We also performed qPCRs experiments to quantify the mRNA levels for the aha-1 gene from bulk RNA extractions from adult worms.ResultsWe observed robust luminescent circadian rhythms driven by the aha-1 promoter. However, aha-1 mRNA levels did not show circadian oscillation under the conditions tested. We also show that a mutation in aha-1 generates a significantly longer endogenous period than the one in control strains, suggesting a role for this gene in the nematode circadian clock.ConclusionThe results indicate that the CYCLE/BMAL-1 homolog AHA-1 plays a key role in the generation of circadian rhythms in adult nematodes, mainly by regulating period length. These results suggest that the molecular control of circadian regulation in C. elegans exhibits some similarities to other clock model systems.